2011
DOI: 10.3892/ijo.2011.1202
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation for hepatocellular carcinoma induces glypican-3 peptide-specific cytotoxic T lymphocytes

Abstract: Abstract. Glypican-3 (GPC3), a carcinoembryonic antigen, is an ideal target for anticancer immunotherapy against hepatocellular carcinoma (HCC). In this study, we attempted to compare the induction of the GPC3-specific T-cell-mediated immune response after locoregional therapies in HCC patients and tumor-bearing mice. Twenty-seven HCC patients treated with locoregional therapies, including radiofrequency ablation (RFA), surgical resection and transcatheter arterial chemoembolization (TACE), were prospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 31 publications
0
35
0
Order By: Relevance
“…It has been shown that RFA induced systemic tumor-antigen T cell immune responses in human hepatocellular carcinoma (8, 9). However, these studies are limited to the analysis of peripheral immune cells but not in TME.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that RFA induced systemic tumor-antigen T cell immune responses in human hepatocellular carcinoma (8, 9). However, these studies are limited to the analysis of peripheral immune cells but not in TME.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on preclinical animal models have shown that localized tumor ablation by RFA can induce systemic T-cell mediated antitumor immunity (5-7). Antigen-specific T cell immune responses were also observed in patients with hepatic tumors after RFA therapy (8, 9). However, the RFA-induced immune responses are not sufficient to prevent tumor recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…RFA was applied to a tumor on one side, when subcutaneous tumors grew up to about 5 mm in diameter, followed by injec5on of 1×10 7 DCs into the treated tumor with RFA. Untreated tumor on the opposite side was observed for 10 days.…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%
“…Recently, RFA has been used as an adjunct to hepatic resection, or as an alternative method to resection when surgical treatment is not feasible [5]. Additionally, it has been revealed that RFA for metastatic liver cancers generates tumor antigen-specific T-cell responses in man [6,7]. We have previously reported that RFA could also control distant tumor growth in a murine hepatocellular carcinoma (HCC) model [8].…”
Section: Introductionmentioning
confidence: 99%
“…Transarterial embolization, for example, not only induced tumor necrosis directly, but also expanded the T cell-mediated immune response [57]. Additionally, Nobuoka and co-workers reported that radiofrequency HCC ablation induced peptide-specific CTLs [58]. Such studies provide a rationale for combining ASPH-based immunotherapy with additional approaches to optimize treatment of HCC.…”
Section: Discussionmentioning
confidence: 99%